Isolation, identification, and analysis of the invertase-producing bacteria abundance in sugarcane rhizosphere soil with different plant productivity levels - Ester Raisa K. Lase; Giyanto Giyanto; DWI ANDREAS SANTOSA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Lase ERK, Giyanto Santosa DA. 2021. Isolation, identification, and analysis of the invertase-producing bacteria abundance in sugarcane rhizosphere soil with different plant productivity levels. Biodiversitas 22: 3156-3162. microbes and enzymes play an important role in maintaining the stability of soil ecosystems. Invertase is one of the soil enzymes produced by microbes to hydrolyze sucrose in the environment. The aims of this study were to investigate the abundance of invertase-producing bacteria and soil invertase activity in sugarcane rhizosphere soil with different plant productivity levels and their correlation with soil chemical and physical properties and to obtain invertase-producing bacteria from the sugarcane rhizosphere. The samples of sugarcane rhizosphere soil were collected using a randomized sampling method and determine their physical-chemical properties, the abundance of invertase-producing bacteria, and soil invertase activity. Twenty invertase-producing bacteria were successfully isolated and tested their abilities to produce invertase qualitatively and quantitatively. The three best isolates (ScT112, ScT124, and ScR301) were molecularly identified using the 16S rRNA gene and phylogenetic tree analysis. The results of this study indicate that there is a significant correlation between invertase bacterial abundance and soil invertase activity. The abundance of invertase-producing bacteria correlates with pH, organic C, total N, and soil sand content. Invertase activity in the soil correlates with pH and organic C. Based on the phylogenetic tree, the isolates of ScT112 had the closest homology with Cupriavidus sp., ScT124 was homologous with Klebsiella variicola, while ScR301 was homologous with Pantoea sp. These three isolates have the potential to be developed in industrial biotechnology to produce invertase. The hydrolysis zones of ScT112, ScT124, and ScR301 were 3.12 cm, 2.76 cm, and 2.55 cm, respectively with the invertase activity of 27.82 U mL-1, 24.56 U mL-1, and 24.08 U mL-1.